Ceruloplasmin functional changes in Parkinson's disease-cerebrospinal fluid. Issue 1 (December 2015) - Barbariga, Marco; Curnis, Flavio; Andolfo, Annapaola; Zanardi, Alan; Lazzaro, Massimo; Conti, Antonio; Magnani, Giuseppe; Volontè, Maria; Ferrari, Laura; Comi, Giancarlo; Corti, Angelo; Alessio, Massimo
Abstract Background Ceruloplasmin, a ferroxidase present in cerebrospinal fluid (CSF), plays a role in iron homeostasis protecting tissues from oxidative damage. Its reduced enzymatic activity was reported in Parkinson's disease (PD) contributing to the pathological iron accumulation. We previously showed that ceruloplasmin is modified by oxidationin vivo, and, in addition, in vitro by deamidation of specific NGR-motifs that foster the gain of integrin-binding function. Here we investigated whether the loss of ceruloplasmin ferroxidase activity in the CSF of PD patients was accompanied by NGR-motifs deamidation and gain of function. Results We have found that endogenous ceruloplasmin in the CSF of PD patients showed structural changes, deamidation of the962 NGR-motif which is usually hidden within the ceruloplasmin structure, and the gain of integrin-binding function. These effects occur owing to the presence of abnormal levels of hydrogen peroxide we detected in the CSF of PD patients. Interestingly, the pathological CSF's environment of PD patients promoted the same modifications in the exogenously added ceruloplasmin, which in turn resulted in loss of ferroxidase-activity and acquisition of integrin-binding properties. Conclusions We show that in pathological oxidative environment of PD-CSF the endogenous ceruloplasmin, in addition to loss-of-ferroxidase function, is modified as to gain integrin-binding function. These findings, beside the known role of ceruloplasmin in iron homeostasis, might have important pathogenic implications due to the potential triggering of signals mediated by the unusual integrin binding in cells of central nervous system. Furthermore, there are pharmacological implications because, based on data obtained in murine models, the administration of ceruloplasmin has been proposed as potential therapeutic treatment of PD, however, the observed CSF's pro-oxidant properties raise the possibility that in human the ceruloplasmin-based therapeutic approach might not be efficacious.